Is there a retirement consumption puzzle in Japan? Evidence from a household panel dataset spanning several years. Issue 16 (3rd April 2019) - Hori, Masahiro; Murata, Keiko
ABSTRACT: Using a unique long-run panel of Japanese households, this paper examines the changes in consumption at retirement ('the retirement-consumption puzzle'). Our analysis shows that households' expenditure does decline after the retirement of the household head and that changes in household composition at retirement cannot fully account for this decline. Changes in life-style/preferences after retirement also do not appear to explain a salient feature of the expenditure decline, namely, the strong correlation between the magnitudes of the expenditure decline and the income decline upon retirement. On the other hand, our finding that the expenditure decline is larger for households with smaller savings and/or that experienced a large unexpected income decline is broadly consistent with the standard LC/PIH augmented with unexpected shocks, while it does not rule out the possibility that there is a relatively small subset of households that are myopic and lack sufficient saving discipline.